2016
DOI: 10.1007/s10620-016-4104-7
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Fecal Calprotectin Levels and Small-bowel Inflammation Score in Capsule Endoscopy: A Multicenter Retrospective Study

Abstract: LS appears to show low correlation with FC as well as other serology markers of inflammation. FC does not appear to be a reliable biomarker for significant small-bowel inflammation. Nevertheless, FC level ≥ 76 μg/g may be associated with appreciable visual inflammation on small-bowel CE in patients with negative prior diagnostic workup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…If physicians can ignore small lesions to consider the long-term outcome of CD, abdominal ultrasonography and magnetic resonance enterography (MRE) will also be excellent modalities to evaluate MH. Koulaouzidis et al reported that the LS appears to have only a fair correlation with the FC level, as well as other serological markers of inflammation [ 33 ]. FC level does not seem to be a reliable biomarker for significant SB inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…If physicians can ignore small lesions to consider the long-term outcome of CD, abdominal ultrasonography and magnetic resonance enterography (MRE) will also be excellent modalities to evaluate MH. Koulaouzidis et al reported that the LS appears to have only a fair correlation with the FC level, as well as other serological markers of inflammation [ 33 ]. FC level does not seem to be a reliable biomarker for significant SB inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Two additional studies published since also provided evidence in support of this notion [ 25 , 26 ]. On the other hand, some studies have shown that the correlation between FCP and objective assessment of the SB inflammation such as the validated LS is equivocal or moderate at best [ 27 , 28 ]. This may have been influenced by the retrospective nature of these studies or inherently within the LS itself, as the presence of a stricture without an associated inflammation will significantly increase the score but may not be associated with a corresponding increase in FCP.…”
Section: Discussionmentioning
confidence: 99%
“…With a limited number of observations, this finding should be interpreted carefully, especially because patients with L1 tended to have a relatively mild disease. Nevertheless, proximal CD detection by measuring SC is problematic, and parallel quantification of calprotectin and EDN may reduce risk of false‐negative results. We combined calprotectin and EDN measurements in the CALEDN test, and this modification resulted in increasing both AUC and sensitivity values.…”
Section: Discussionmentioning
confidence: 99%